Plantas tóxicas para ruminantes e equídeos na região central de Rondônia - Schons, Sandro de Vargas (2011)
A survey about the presence of toxic plants and the occurrence of outbreaks of poisoning in ruminants and horses was performed in 12 municipalities of the central region of the state of Rondônia. Ninety eight persons were interviewed, including farmers, veterinary practitioners, agronomists, and agrarian technicians. Sixteen plants, previously known as toxic, were mentioned by the interviewed, including Palicourea marcgravii in 80% of the interviews, Asclepias curassavica in 79%, Palicourea grandiflora in 67%, Brachiaria spp. in 66%, Enterolobium contortisiliquum in 65%, Pteridium aquilium em 57%, Brachiaria radicans in 50%, Lantana camara in 47%, Senna occidentalis in 40%, Ricinus communis in 33%, Manihot esculenta in 33%, Ipomea carnea in 20%, Ipomoea asarifolia in 17%, Palicourea juruana in 17%, Crotalaria spp. in 16%, and Arrabidaea bilabiata in 6%. Thirty four farmers reported poisoning by toxic plants, including poisoning by Palicourea marcgravii (12 outbreaks), Palicourea grandiflora and Enterolobium contortisiliquum (seven outbreaks each), and Palicourea juruana, Brachiaria radicans, Brachiaria brizantha, and Manihot esculenta (two outbreaks each). In sheep, farmers reported two outbreaks of photosensitization caused by Brachiaria decumbens and one outbreak of sudden death caused by Palicourea grandiflora. In the 34 outbreaks, 374 (8,9%) bovines were affected and 311 (7,4%) died, from a total of 4.192 cattle exposed. In the three outbreaks in sheep, 28 animals were affected and 20 died out of 250 exposed. Amorimia sepium, a previously unreported toxic plant, was identified as a cause of sudden death in sheep and cattle in 32% of the farms. Fifteen outbreaks of colic in horses grazing Panicum maximum (cultivars Massai, Tanzânia, and Mombaça) during the rainy season were also reported. Experiments were conducted with Enterolobium spp., Amorimia sepium and Panicum maximum. It is concluded that poisoning by toxic plants is an important cause of economic losses in livestock in the region studied. With the results of this research the number of known toxic plant for ruminants in central region of Rondônia increased from one to nine, indicating that more research is necessary for the knowledge of poisonous plants for livestock in the Brazilian Amazonic region.